Optimization of mining methods for deep orebody of large phosphate mines - Hou, Di; Xu, Mengchao; Li, Xiaoshuang; Wang, Jiawen; Wang, Menglai; Li, Shujian (Frontiers in Built Environment, 2023)
Introduction: Taking Yunnan Phosphate Group Co., Ltd. Kunyang Phosphate Mine No. 2 as the engineering background, this study aims to explore mining methods for deep ore bodies in phosphorus mines. Three mining schemes, namely open-pit mining, open-pit deep concave mining, and underground mining, were carefully selected for optimization. This article thoroughly analyzes the three schemes from various perspectives, including technical, economic, safety, and other aspects. Methods: The assessment of these aspects was conducted using the entropy weighted TOPSIS method. The technical aspects focused on evaluating the mining methods employed in each scheme. The economic aspects considered factors such as initial investment, resource recovery rate, phosphate content, production scale, infrastructure, and mining costs. Safety aspects took into account transportation safety and production safety. Additionally, the analysis considered environmental impact as one of the key factors. In total, 10 indicators were quantified to provide a comprehensive evaluation. To assess the schemes, the positive and negative ideal distances (Di+, Di−) and the relative proximity (Ci) for open-pit mining, open-pit deep concave mining, and open-pit to underground mining were calculated. These calculations helped to determine the relative performance of each scheme. Results: The relative closeness values (Ci) for Scheme 1, Scheme 2, and Scheme 3 are determined as 1.00, 0.09, and 0.68, respectively.The evaluation results indicate that the relative closeness (Ci) for open-pit mining in Scheme 1 is 1.00, for open-pit deep concave mining in Scheme 2 is 0.09, and for underground mining in Scheme 3 is 0.68. Through comparison and analysis of these results, it can be concluded that open-pit mining is the most optimal method. However, considering the fact that the open-pit portion of Kunyang Phosphate Mine No. 2 has already been extensively mined, the study recommends underground mining as the best mining plan for the phosphate mine. Discussion: By applying the entropy weight TOPSIS method to underground mining, this study overcomes the challenge of transitioning from qualitative to quantitative analysis for selecting mining methods. The mathematical approach enables the presentation of optimal mining techniques in a more precise manner. Through comparison of relative closeness, an optimal solution can be selected. This method holds significant value not only for selecting suitable mining methods for phosphorus mines but also for choosing optimal solutions for underground mining methods, drainage, ventilation, and other relevant considerations.